International development cooperation theory, practice, and evaluation - Zhao, Jianzhi; Lin, Qin (New Jersey World Scientific, 2023)
This book studies the theory, practice and evaluation methods of international development cooperation, aid and assistance management in detail from a global perspective. It attempts to answer the following questions: How effective are the current Western aid methods? How should China optimize current international development cooperation? How to effectively design an aid management system in the international community? How to assess the effectiveness of aid? The book contributes to studies in international development cooperation. The theoretical part analyzes the main concepts, viewpoints, theories, and disputes in current international development cooperation, primarily focusing on the differences in concepts between traditional development donors and emerging donors represented by China. The practical part studies the roles and importance of different subjects in international development assistance. This part also explores the impact of different aid management institutions on international development cooperation. The evaluation part reviews the current mainstream methods of international development assessment and uses non-experimental methods of impact evaluation and randomized controlled trials (RCTs)"--
Contents: PART 1: Theory of International Development Cooperation: Chapter 1: Definition of International Development Assistance - - Chapter 2: Research on the Effectiveness of International Development Assistance - - Chapter 3: International Development Cooperation Models and China's Experience - - PART 2: Practice of International Development Cooperation: Chapter 4: Introduction to the Management Systems of International Development Cooperation - - Chapter 5: Participants in International Development Cooperation - - Chapter 6: A Comparison of the Aid Management Systems of Traditional Donor Countries - - Chapter 7: A Comparison of the Aid Management Systems of Emerging Donor Countries - - PART 3: Evaluation of International Development Projects: Chapter 8: Introduction to Evaluation of International Development Projects.
Originally published in Chinese by China Social Sciences Press.
Includes bibliographical references and index.
Keywords: Economic assistance, Chinese; Economic assistance; International economic relations; China -- Foreign economic relations